Migratory experiences of purépecha indians in Nezahualcoyotl, State of México - Sánchez Villal, Martin; Bautista Miranda, Miguel (Trabajo Social UNAM, 2016)
The objective of the present article is to ponder the life story of the Purépecha Indian immigrant population who are confronted with processes and change and cultural continuity upon their arrival in the Township of Nezahualcóyotl, State of Mexico. This is an exploratory study and therefore does not lead to the creation of determinant conclusions. We base our study on Geertz’ (2005) work on studying the processes of social significance and we incorporate Thompson (2006) in order to take a glimpse at the structures of power. Evidence shows that Indians design various strategies which put them in constant negotiation and resistance to conserve and assign new meaning to their Indian identity in the face of vulnerability, marginalization and social rejection to which they are subjected. We take up the cases of three Purépecha Indians living in Nezahualcoyotl, in order to develop the interpretation of changes and continuities of their identities based on a series of practices and strategies they have elaborated, both coercively and voluntarily.